Board member remuneration and earnings management: The case of Portugal - Dias, C.; Paiva, I.; Carvalho, Luísa Cagica (Administrative Sciences, 2024)
This study draws on agency theory and evaluates the effect of the remuneration structures of board members on earnings management, proxied by discretionary accruals. To achieve the objective, this study uses a multiple regression model and a hand-collected dataset of Portuguese-listed firms from 2015 to 2019. This study suggests that fixed board remuneration is associated with lower levels of earnings management, as opposed to variable remuneration of board members, which is strongly associated with a higher level of earnings management. The findings based on this study provide useful information to investors and regulators in evaluating the effect of board compensation structure on earnings management. Additionally, this study expands the corporate governance literature by examining an under-researched mechanism to address the agency problem.